2018
DOI: 10.1038/s41390-018-0115-8
|View full text |Cite
|
Sign up to set email alerts
|

The long-term effect of perinatal asphyxia on hippocampal volumes

Abstract: Children with moderate HIE had smaller hippocampal volumes than controls, with a trend toward smaller volumes following mild HIE. Reduced hippocampal volumes were associated with poorer long-term visuospatial memory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 37 publications
2
31
0
Order By: Relevance
“…In this study, we have demonstrated that this novel and simple prenatal hypoxia protocol recapitulates several key features seen in children born after mild HIE, including deficits in anxiety [59], motor function [60], and susceptibility to seizures [4,58]. These functional deficits occur in the absence of long term structural deficits, which is also consistent with lack of gross anatomic deficits in children with mild HIE [4,61]. Together these data suggest that this model of transient prenatal hypoxia is most similar to mild neurodevelopmental deficits after mild HIE, a clinically important group of patients.…”
Section: Discussion/conclusionsupporting
confidence: 71%
See 1 more Smart Citation
“…In this study, we have demonstrated that this novel and simple prenatal hypoxia protocol recapitulates several key features seen in children born after mild HIE, including deficits in anxiety [59], motor function [60], and susceptibility to seizures [4,58]. These functional deficits occur in the absence of long term structural deficits, which is also consistent with lack of gross anatomic deficits in children with mild HIE [4,61]. Together these data suggest that this model of transient prenatal hypoxia is most similar to mild neurodevelopmental deficits after mild HIE, a clinically important group of patients.…”
Section: Discussion/conclusionsupporting
confidence: 71%
“…Some if these deficits are analogous to neurodevelopmental disabilities seen in children after HIE, including in deficits in anxiety [59], motor function [60], and susceptibility to seizures [4, 61]. The functional deficits in the absence of long-term structural deficits is also consistent with lack of gross anatomic deficits in children with mild HIE [4, 62]. This model did not, however, demonstrate significant deficits in motor learning or visual-spatial learning that would more directly correlate to cognitive deficits sometimes seen in these children [7].…”
Section: Discussion/conclusionmentioning
confidence: 97%
“…Thus, perinatal hypoxia has been shown to account for the subsequent profile of long-term cognitive impairment in the general population 45 . For example, one study showed that compared to controls, children with perinatal asphyxia had smaller hippocampal volumes that were associated with poorer long-term visuospatial memory 46 . Another study showed that even mild oxygen deprivation at, or immediately after, birth was related to an increased risk of developmental delays later in childhood: those with mild to moderate acidosis (a measure of risk of hypoxia) displayed significantly lower (p < 0.05) verbal and visuospatial test scores than the low-risk group 47 .…”
Section: Introductionmentioning
confidence: 99%
“…In the Netherlands, infants with HIE are currently followed in the outpatient clinics until 5.5 years of age. As shown in this thesis and by others, some deficits, such as memory problems or behavioral problems, only become evident at school-age (1,(30)(31)(32)66,67).…”
Section: Long-term Follow-upmentioning
confidence: 55%
“…According to a growing number of studies, 7.0T MRI enables better visualization of micro-bleedings and the microcirculation at SWI, MRA and MRV, detection of additional metabolites at MRS and better quality of T2-weighted imaging that allows to see more details of the anatomy i.e. the different layers of the cortex can be distinguished (66). In infants 7.0T MRI might also be beneficial to optimize MRI quality, but so far this has never been performed.…”
Section: Innovative Neuroimaging Methodsmentioning
confidence: 99%